THE EPIDEMIOLOGY OF COVID-19 IN PANDEYAN UMBULHARJO, YOGYAKARTA CITY IN 2021 - Ria, Dana Asta; Sulistyawati, Sulistyawati; Padmawati, Ike Lukita; Rahastri, Ajeng (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: COVID-19 is an acute respiratory infection caused by the Coronavirus, known as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The emergence of COVID-19 has affected the health conditions of all countries, especially Indonesia. Efforts to prevent and control the spread of cases include conducting epidemiological investigations. Indonesia uses community health centres as primary health services to prevent transmission through surveillance systems such as epidemiological investigations. This research describes the epidemiological of COVID-19 in the Pandeyan region of Umbulharjo Yogyakarta City from June to August 2021. Objective: This study aims to describe the epidemiology of COVID-19 cases in the Pandeyan, Umbulharjo Yogyakarta City from June to August 2021. Method: This was quantitative descriptive research using secondary data from epidemiology investigation. The population in this study was all people who were the target of Epidemiology Investigation in Pandeyan, Umbulharjo, in June-August 2021, namely 477 perople. The sample was taken by total sampling. The instrument used was the Epidemiological Investigation Form (PE) result. Results: The most cases of COVID-19 were women, namely 271 (56.81%), with the most extensive age range being 26-35 years, namely 94 cases. The most cases of COVID-19 were found in RW 6, Pandenyan (107 cases). In July 2021, 260 cases were reported; the highest cases were on June 30, 2021. Conclusion: COVID-19 cases are often found in RW 6, Pandeyan, Umbulharjo. In July 2021, as many as 260 cases were reported, and a spike in daily cases was observed on June 30, 2021.